Reproductive and genotoxic effects of dinotefuran in male Sprague Dawley rats - A. G. Abdelkader; W. H. Mohamed; M. Abou-Ellail; K. A. Amein (Bulgarian Journal of Veterinary Medicine)
The objective of the current study was the evaluation of the genotoxic and reproductive effects of dinotefuran (DIN) insecticide in male Sprague Dawley rats. To achieve these objectives, forty male 10–12 weeks old Sprague Dawley rats were randomly divided into four equal groups; the first group was used as a control group; the other three groups were exposed to 40, 61, and 122 mg/kg body weight DIN by oral gavage for 8 weeks. Relative testicular weight, testosterone, follicle stimulating hormone (FSH), luteinizing hormone (LH), malondialdehyde (MDA) and glutathione peroxidase (GPx) levels, sperm viability, sperm morphology, chromosomal aberrations assay, expression of inter-leukin 6 (IL-6) and cluster of differentiation 68 (CD68), and histopathological changes in testes of these rats were examined after 8 weeks. The results showed that DIN exposure resulted in a signifi-cant increase in testosterone, the percentage of dead and abnormal sperms, the percentage of meta-phase cells with chromosomal aberrations, and expression of IL-6 and CD-68 but decreased GPx levels. Histopathological examination of the testes revealed hypertrophied seminiferous tubules of testes with a disrupted arrangement of germinal epithelial cells accompanied by many necrotic areas. It was concluded that exposure to DIN for 8 weeks induced hazardous impacts on the reproductive system and caused genotoxicity.